The importance of intergenerational stability for the social origins of undereducation and overeducation. (April 2023) - Bürmann, Marvin
Abstract: Only recently have sociologists begun to examine the social origins of educational mismatches in more detail. This research not only repeatedly found, but also investigated why individuals from lower social origin more often have a higher level of education than required for their job (overeducation), and why individuals from a higher social origin more often realize high positions despite having a lower level of education than required for their job (undereducation). While these studies provide additional and valuable empirical insights into the effect of social origin on both types of mismatch separately, to date there has been no investigation on general sociological meaningful conditions, under which the social origin unfolds an effect on undereducation and overeducation in the first place. This paper addresses this gap by examining the relevance of intergenerational stability for the effect of social origin on mismatches. It does so by drawing on arguments from sociological theories on intergenerational (im-)mobility, data from the German Socio-Economic Panel (SOEP) for the period 1990–2017, and two different measurement methods for educational mismatches. The empirical results show evidence of substantial heterogeneity in the effect of social origin on educational mismatches: A higher parental status is found to be advantageous only for employees with intergenerational stability in social classes and/or occupational tasks. This indicates that the intergenerational transmission of class-specific traits and occupational skills contribute to the effect of social origin on mismatches. The results show no effect of parental status on educational mismatches among employees who are intergenerationally mobile and make up half of the German labor force under investigation. Since this heterogeneity is also found among workers who immigrated to Germany as adults, parental networks within Germany and the corresponding social capital can be ruled out as the main driver behind this finding. Although educational attainment is the most important pathway of intergenerational status maintenance, the results suggest that educational mismatches offer a means of identifying systematic deviations from this pathway. Individuals who follow in the footsteps of their high-status parents are more likely to be employed either at or above their level of education. In the light of the strong heterogeneity revealed, complementary explanations and routes for further research to investigate the link between intergenerational (im-)mobility, social origin and educational mismatches are discussed.